The Role of Himpaudi in the Development of PAUD Educators’ Competence in Semarang City - Listyowati, Listyowati (Jurusan PGPAUD FIP UNNES, 2017)
This study begins from the importance of developing the competence of PAUD educators in Semarang City. It caused by the variations of educational level qualifications that ultimately affect the competence of PAUD educators. The objective of this study is to examine the role of HIMPAUDI of Semarang in developing the competence of PAUD educators and the factors that inhibit the development of PAUD educators’ competence in the Semarang. This study uses qualitative approach with descriptive method and the instruments of the data collection are interview, observation and documentation.The findings of this study shows that the planning of PAUD educators’ competence development program done through the analysis of the identification of PAUD educators’ needs, so that the improvement of PAUD educators’ competence program is expected to solve their problems. The program of increasing the competence of PAUD educators implemented in the main program, that are tiered training, seminars, workshop and competitions for PAUD educators. To follow up the program of increasing the competence of PAUD educators, HIMPAUDI conducted an assessment by monitoring the progress of PAUD educators through HIMPAUDI branch and involving principals at PAUD institutions in Semarang. There are some obstacles in the effort of developing the competence of PAUD educators; funding, communication and determining the appropriate activity for the development of personality and social competence of PAUD educators.